Clinical characterization of the first Belgian SCN5A founder mutation cohort. Issue 6 (22nd November 2020) - Sieliwonczyk, Ewa; Alaerts, Maaike; Robyns, Tomas; Schepers, Dorien; Claes, Charlotte; Corveleyn, Anniek; Willems, Rik; Van Craenenbroeck, Emeline M; Simons, Eline; Nijak, Aleksandra; Vandendriessche, Bert; Mortier, Geert; et al.
Abstract: Aims: We identified the first Belgian SCN5A founder mutation, c.4813 + 3_4813 + 6dupGGGT. To describe the clinical spectrum and disease severity associated with this mutation, clinical data of 101 SCN5A founder mutation carriers and 46 non-mutation carrying family members from 25 Belgian families were collected. Methods and results: The SCN5A founder mutation was confirmed by haplotype analysis. The clinical history and electrocardiographic parameters of the mutation carriers and their family members were gathered and compared. A cardiac electrical abnormality was observed in the majority (82%) of the mutation carriers. Cardiac conduction defects, defined as PR or QRS prolongation on electrocardiogram (ECG), were most frequent, occurring in 65% of the mutation carriers. Brugada syndrome (BrS) was the second most prevalent phenotype identified in 52%, followed by atrial dysrythmia in 11%. Overall, 33% of tested mutation carriers had a normal sodium channel blocker test. Negative tests were more common in family members distantly related to the proband. Overall, 23% of the mutation carriers were symptomatic, with 8% displaying major adverse events. As many as 13% of the patients tested with a sodium blocker developed ventricular arrhythmia. One family member who did not carry the founder mutation was diagnosed with BrS. Conclusion: The high prevalence of symptoms and sensitivity to sodium channel blockers in our founder population highlights the adverse effect of the founder mutation on cardiac conduction. The large phenotypical heterogeneity, variable penetrance, and even non-segregation suggest that other genetic (and environmental) factors modify the disease expression, severity, and outcome in these families.